Publishing Research in English as an Additional Language: Practices, Pathways and Potentials - Burgess, Sally; Cargill, Margaret (University of Adelaide Press, 2017)
Many universities worldwide now require established and novice scholars, as well as PhD students, to publish in English in international journals. This growing trend gives rise to multiple interrelated questions, which this volume seeks to address through the perspectives of a group of researchers and practitioners who met in Coimbra, Portugal in 2015 for the PRISEAL and MET conferences. The volume offers truly global coverage, with chapters focusing on vastly different geo-social areas, and disciplines from the humanities to the hard sciences. It will be of interest to applied linguists, particularly those working in the area of English for Research Publication Purposes, and to language professionals working in research writing support, research supervision and academic publishing, as well as to journal editors and managers.